The Blind Side of Public Debt Spikes - Jaramillo, Laura (IMF Working Papers; Working Paper ;, 2016)
What explains public debt spikes since the end of WWII? To answer this question, this paper identifies 179 debt spike episodes from 1945 to 2014 across advanced and developing countries. We find that debt spikes are not rare events and their probability increases with time. We then show that large public debt spikes are neither driven by high primary deficits nor by output declines but instead by sizable stock-flow adjustments (SFAs). We also find that SFAs are poorly forecasted, which can affect debt sustainability analyses, and are associated with a higher probability of suffering non-declining debt paths in the aftermath of public debt spikes.